Adaptação marginal de copings de três sistemas cerâmicos em função de dois tipos diferentes de terminação cervical - Oliveira, Alberto Alvarenga de (2007)
The objective of this work was to evaluate in vitro the accuracy of marginal foundation of copings of three ceramic systems: In-Ceram; IPS Empress 2 and Procera All Ceram. Besides, two variations of differents cervical terminations were established: shoulder 90o and chamfer. In order to do this, two superior central incisors of identical models received standardized cavity prepare for total crown, varying the cervical termination only, in a way that one received termination in shoulder 90o with a round internal angle and other, chamfer. Therefore, six kinds of treatments were established: IO (In-Ceram/Shoulder); IC (In-Ceram/Chamfer); EO (Empress/Shoulder); EC (Empress/Chamfer); PO (Procera/ Shoulder); PC (Procera/Chamfer). For the manufacturing of copings, the prepared teeth were reproduced in dental stone singles dies by means of standardized impressions with addition silicon, where seventy two copings were manufactured, subdivided in three groups of twenty four each type of ceramic material. Within each group, half of the substructures were built for prepare with cervical termination in shoulder 90o and the other half for cervical termination in chamfer. The marginal disadjustment of copings was evaluated and measured in optic microscopy, with a forty times enlargement, from observation of moulds of the marginal fissure of each sample with addition silicon of fluid consistency. For each sample, twelve measurements were taken and the average results showed a variation of 23,08 to 36,11um. The groups PO and PC of the Procera system presented the best results (23,08 and 25,77um respectively) and differed statistically from the IO group (36,11um) that presented the worst average result. Among the other groups there was no significant statistic difference and the average results were: IC (28,46um); EO (29,51um); EC (27,94um). In relation to the kinds of cervical termination, the statistic analysis was not conclusive, although a better behaviour of the chamfer could be suggested, because the groups with this kind of cervical termination presented low average deviations in comparison to the groups with shoulder 90o . Due to the obtained results we can conclude that the average results of all the studied treatments were within the established clinical acceptability of 120um.